Follistatin‐like protein 5 inhibits hepatocellular carcinoma progression by inducing caspase‐dependent apoptosis and regulating Bcl‐2 family proteins. Issue 12 (25th September 2018) - Li, Chunlei; Dai, Lei; Zhang, Junfeng; Zhang, Yujing; Lin, Yi; Cheng, Lin; Tian, Hongwei; Zhang, Xin; Wang, Qingnan; Yang, Qianmei; Wang, Yuan; Shi, Gang; et al.
Abstract: Hepatocellular carcinoma (HCC) is one of the most common and deadly malignant tumors in the world, especially in China. Follistatin‐like protein 5 (FSTL5) is a member of the FSTL family, which is involved in cell proliferation, migration, differentiation, and embryo development. We aimed to investigate the function and underlying mechanism of FSTL5 in HCC. FSTL5 expression was determined by immunohistochemistry staining in a liver cancer tissue microarray (TMA) and the correlation between FSTL5 and the prognosis of HCC patients was analysed. Further proliferation assay, colony formation assay, flow cytometry, and xenograft tumor model were performed to investigate the bioeffects of FSTL5 in HCC in vitro and in vivo. We found that FSTL5 expression was downregulated in HCC tissues and positively correlated with the prognosis of patients with HCC at tumor node metastasis stage I/II. Overexpression of FSTL5 efficiently impaired HCC growth both in vivo and in vitro with an exogenous manner. Mechanistic investigation demonstrated that FSTL5 promoted HCC cell apoptosis in a caspase‐dependent manner and regulated Bcl‐2 family proteins. These results indicate that FSTL5 may be a potential novel target for HCC treatment, and a biomarker for tumor prognosis.